Counseling Leaflet Methods And Social Media To Change Knowledge Of Pregnant Women In The Third Trimester At Salassae Health Center - Asmirati; Marwidah; Mitra Asriani; Irmawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
Family planning is an example of direct policy in the field of population control. Strategic intervention in safe motherhood efforts is expressed as 4 pillars namely family planning, antenatal care, clean and safe delivery, and essential obstetric services. The development of new media based on the internet has greatly influenced media consumption patterns in Indonesian society. The study used experimental quasi research designs with group pre-test and post-test designs. It used 100 respondents as selected samples using Purposive Sampling. The results of the statistical signed-rank test were obtained on average the knowledge of respondents before being given intervention with a leaflet of 9.76 while after being given intervention 16.34 with P value (Asymp). Sig. (2-tailed)) 0,000 where <0.05 so that it can be concluded that there are significant differences before and after respondents are given intervention with leaflets. The average value before being given intervention in the form of social media Whatsaap amounted to 8.54 while after being given an average value of 17.72 with an average value of 17.72 with P value (Asymp). Sig. (2-tailed)). Based on the results of the Wilcoxon statistics test sum rank test or commonly called Mann-Whitney u test obtained a mean leaflet value of 35.85 while Whatsapp social media amounted to 65.15 with a p-value of 0.00. This proves that WhatsApp social media has a greater influence in increasing knowledge compared to leaflet media.